THE EFFECT OF A TRAINING PROGRAM USING TABATA TRAINING ON MUSCLE ENDURANCE AND SOME PHYSIOLOGICAL VARIABLES IN BASKETBALL PLAYERS - Waleed Kamil Rashoody; Karar Jaafar Abas (Proximus Journal Publishing, 2025)
The study aims to use high-intensity training for relatively short periods of time. The researchers focused their research on finding exercises that aim to make the body exert the maximum possible effort and bring its muscles to the maximum possible level of performance This is done by relying on the body’s internal effort and energy without external effort and heavy weights to know the effect of these exercises on muscle endurance and their physiological effects on basketball players. The researchers chose their research sample intentionally, which is the players of the National Center for Sports Talent Care in Diwaniyah, numbering 10 players The researchers used the experimental method with the single-group approach to suit the research problem. The researchers conducted homogeneity for the players. In this study, the researchers targeted some variables and applied them to their research sample, which are muscular endurance, lactic acid tolerance, and heart rate. The method took a period of four weeks, with four training units per day The duration of the training units lasted from 50-60 minutes in each training unit and throughout the period of implementing the training program in order to know the effect of those exercises on those studied variables. After that, the researchers used statistical treatments for their training program in order to reach the clear effect of those exercises on the studied variables Statistics showed that Tabata exercises had a significant impact on the variables studied. In light of these results, the researchers explained their conclusions and recommendations based on the results obtained, as well as some important recommendations regarding this study What was reached after that is that Tabata exercises have a large and clear effect on the studied variables: muscular endurance, lactic acid tolerance, and also heart rate
Keywords: Tabata training; Muscle endurance; Lactic acid